AYURGENOMICS: A BRIEF NOTE ON AYURVEDA AND THEIR CROSS KINGDOM GENOMICS (International Association of Biologicals and Computational Digest, 2022)
Genomics has led in an era of prognostic, defensive and personalized medicine wherein it is expected that not too far in the future there would be a prototype shift in the practice of medicine from a generalized symptomatic approach to an individualized approach based on his or her genetic makeup. Ayurveda, an ancient Indian system of medicine recognized and experienced in India since 1500 B.C has personalized methodology towards management of health and disease. We thought an addition of Ayurveda and genomics if endeavoured in an efficient way which we call as Ayurgenomics could assistance fill the gap. MicroRNAs (miRNAs) are a class of noncoding small RNAs, which play a vital character in post- transcriptional gene regulation. Currently, numerous study exposed that miRNAs could be transmitted between species to mediate cross-kingdom regulation by assimilating into a specific target gene-mediated governing pathway to apply applicable biological functions. Here, we discuss probable miRNA parallel transfer appliances from one species to another and analyze the relationship between miRNA-mediated cross-kingdom regulation.
Keywords: Genomics, Ayurveda, Ayurgenomics, miRNAs, cross-kingdom